Density of Sea Urchin Species (Echinoidea) in The Intertidal Zone of Taruan and Gemeh Subdistricts of Gemeh, Talaud Islands Regency - Ronald F. Tegi; Erly Kaligis; Deislie R.H. Kumampung; Natalie D.C. Rumampuk; Farnis Boneka; Billy Th. Wagey (JURNAL PESISIR DAN LAUT TROPIS, 2025)
Sea urchins (Echinoidea) are important organisms in intertidal areas that contribute to maintaining the balance of the coastal marine environment. This study aims to identify the level of diversity, population density, and dominance of sea urchin species found in the intertidal zone of Taruan Village and Gemeh Village, Talaud Islands Regency. Data were collected using the 1 × 1 meter belt transect method in the two locations. The results showed that Taruan Village had more species, namely seven species, compared to Gemeh Village which only had four species. The highest density value was recorded in Taruan at 10.5 ind/m², while in Gemeh it was 6.2 ind/m². The diversity index (H') was in the range of 1.220 to 1.662 and belonged to the medium category, while the dominance index (C) value ranged from 0.230 to 0.324, indicating the absence of a significantly dominating species. Environmental parameters such as salinity, temperature, and pH in both locations are within the range that supports the survival of sea urchins. The results of this study should serve as an initial reference for efforts to conserve and manage sustainable marine resources in the Talaud Island region. Keywords:. sea urchins diversity, density, dominance, Talaud   Abstrak                                          Bulu babi (Echinoidea) merupakan organisme penting di kawasan intertidal yang berkontribusi dalam menjaga keseimbangan lingkungan laut pesisir. Penelitian ini bertujuan untuk menganalisis tingkat keanekaragaman, kepadatan populasi, dan dominansi spesies bulu babi yang terdapat di zona intertidal Desa Taruan dan Desa Gemeh, Kabupaten Kepulauan Talaud. Pengambilan data dilakukan menggunakan metode belt transek berukuran 1×1 meter di dua lokasi tersebut. Hasil pengamatan menunjukkan bahwa Desa Taruan memiliki jumlah spesies lebih banyak, yaitu tujuh spesies, dibandingkan Desa Gemeh yang hanya memiliki empat spesies. Nilai kepadatan tertinggi tercatat di Taruan sebesar 10,5 ind/m², sedangkan di Gemeh sebesar 6,2 ind/m². Indeks keanekaragaman (H') berada pada kisaran 1,220 hingga 1,662 dan tergolong dalam kategori sedang, sedangkan nilai indeks dominansi (C) berkisar antara 0,230 hingga 0,324, yang mengindikasikan tidak adanya spesies yang mendominasi secara signifikan. Parameter lingkungan seperti salinitas, suhu, dan pH di kedua lokasi berada dalam kisaran yang mendukung kelangsungan hidup bulu babi. hasil penelitian ini seharusnya dapat menjadi referensi awal dalam upaya pelestarian dan pengelolaan sumber daya laut yang berkelanjutan di wilayah Kepulauan Talaud. Kata kunci: bulu babi, keanekaragaman, kepadatan, dominansi, Talaud